2022
DOI: 10.3390/pharmaceutics14010186
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the Phenotype of Dedifferentiated Rabbit Chondrocytes by Sesquiterpene Farnesol

Abstract: Osteoarthritis (OA) is a joint disorder characterized by the progressive degeneration of articular cartilage. The phenotype and metabolism behavior of chondrocytes plays crucial roles in maintaining articular cartilage function. Chondrocytes dedifferentiate and lose their cartilage phenotype after successive subcultures or inflammation and synthesize collagen I and X (COL I and COL X). Farnesol, a sesquiterpene compound, has an anti-inflammatory effect and promotes collagen synthesis. However, its potent resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Wu et al also indicated that GAG production resumes and increases in the presence of 0.4 mM farnesol or 0.8 mM Farn/HA. 22 In the present in vivo study, H&E staining revealed that 0.8 mM Farn/HA led to a greater increase in the number of chondrocytes without significant hypertrophy than did 0.4 mM farnesol or HA nanoparticles [ Fig. 3(a) ].…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…Wu et al also indicated that GAG production resumes and increases in the presence of 0.4 mM farnesol or 0.8 mM Farn/HA. 22 In the present in vivo study, H&E staining revealed that 0.8 mM Farn/HA led to a greater increase in the number of chondrocytes without significant hypertrophy than did 0.4 mM farnesol or HA nanoparticles [ Fig. 3(a) ].…”
Section: Discussionsupporting
confidence: 47%
“…We previously noted that farnesol restores the production of chondrogenic COL II and suppress the production of COL I in IL-1β-stimulated dedifferentiated chondrocytes. 22 In addition, treatment with farnesol significantly reduces PGE2 secretion to a level similar to that secreted the normal chondrocytes. PGE2, involved in inflammation and OA symptom development, modulates PGE2-derived signaling and influences chondrocyte metabolism, affecting ECM structure.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations